Elevated exhaled nitric oxide in allergen-provoked asthma is associated with airway epithelial iNOS. - Abraham B Roos; Michiko Mori; Reidar Grönneberg; Christina Österlund; Hans-Erik Claesson; Jan Wahlström; Johan Grunewald; Anders Eklund; Jonas S Erjefält; Jon O Lundberg; Magnus Nord (PLoS ONE)
Background Fractional exhaled nitric oxide is elevated in allergen-provoked asthma. The cellular and molecular source of the elevated fractional exhaled nitric oxide is, however, uncertain. Objective To investigate whether fractional exhaled nitric oxide is associated with increased airway epithelial inducible nitric oxide synthase (iNOS) in allergen-provoked asthma. Methods Fractional exhaled nitric oxide was measured in healthy controls (n = 14) and allergic asthmatics (n = 12), before and after bronchial provocation to birch pollen out of season. Bronchoscopy was performed before and 24 hours after allergen provocation. Bronchial biopsies and brush biopsies were processed for nitric oxide synthase activity staining with nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d), iNOS immunostaining, or gene expression analysis of iNOS by real-time PCR. NADPH-d and iNOS staining were quantified using automated morphometric analysis. Results Fractional exhaled nitric oxide and expression of iNOS mRNA were significantly higher in un-provoked asthmatics, compared to healthy controls. Allergic asthmatics exhibited a significant elevation of fractional exhaled nitric oxide after allergen provocation, as well as an accumulation of airway eosinophils. Moreover, nitric oxide synthase activity and expression of iNOS was significantly increased in the bronchial epithelium of asthmatics following allergen provocation. Fractional exhaled nitric oxide correlated with eosinophils and iNOS expression. Conclusion Higher fractional exhaled nitric oxide concentration among asthmatics is associated with elevated iNOS mRNA in the bronchial epithelium. Furthermore, our data demonstrates for the first time increased expression and activity of iNOS in the bronchial epithelium after allergen provocation, and thus provide a mechanistic explanation for elevated fractional exhaled nitric oxide in allergen-provoked asthma.